KAJIAN KETERSEDIAAN RUANG TERBUKA HIJAU DI KECAMATAN GONDOKUSUMAN KOTA YOGYAKARTA TAHUN 2009 - , WAHYU TRI W., Drs. Risyanto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Environment quality condition of urban settlement was progressively decreased. In this case, one reason was the growing up of populations which the impact of urbanization was causing city infrastructure facilities increasingly. It causes environment degradation was in the from of decreasingly of green open space condition or green area in varouse places. Open green space was part of city spatial whose be protected areas in the city.Purpose of this research was : (1) finding out the availability of settlement open green space in Gondokusuman Sub District